TO THE QUESTION ABOUT HIGH LEVEL OF LOCAL ENDOGAMY RATES AMONG ETHNIC SWEDES IN KHERSON PROVINCE IN THE XIX – AT THE BEGINNING OF THE XX CENTURY (Південний архів (історичні науки), 2023)
Purpose of the article is to verify popular hypothesis bout high local endogamy rates in Gammalsvenskby colony. It is empirically checking on the base of the parish books information. Methods. Endogamy level is checking through percent of exogamic marriages of Gammalsvenskby inhabitants with settlers from other villages. Gammalsvenskby endogamy is exploring in dynamic, from 1830th to the beginning of XX century. Hypothesis about unique or not unique character of endogamy in Gammalsvenskby are also checking. Gammalsvenskby endogamy rates are comparing with indicators from other Lutheran settlements on the South of Ukraine at the same period. Cohort analysis was using to attempt to explain the reasons of endogamy in the village. Results. Author marks that 96% of marriages among Lutherans on the South of Ukraine in XIX – beginning of XX centuries were concluded within the parish. At the same time, marriages between settlements from different villages in the same parish were very common (near 60% from all marriage cases). It was the same for male and female. Geographical and chronological differences were not detected. The research discovered that the part of exogamic marriages in Gammalsvenskby was half as much than at other settlements in the region and was amount 28%. Gender disparity was also detected (60–65% of exogamous marriages in Gammalsvenskby were conduct by male). Fluctuations of exogamic marriages rates at the village during research period was also find. The number of exogamic marriages cases were decreased when female cohort injured during plague epidemic 1781–1783 years entered the marriage market. Exogamic marriages percent in Gammalsvenskby had a strong increasing trend (local endogamy level was decrease) during research period. Conclusions. Author makes the conclusion that hypothesis about high level of ethnic nationalism in Gammalsvenskby as the main reason of great number of endogamy cases in this village expressed in historiography is unfounded. Strong trend for growing number of exogamic marriages cases contradicts this assumption. Author offer to consider the main reason of high level of endogamy in Gammalsvenskby age and sex composition (decreasing of females in one cohort after plague epidemic).
Keywords: local endogamy, exogamy, marriages, age and sex composition, Gammalsvenskby, Southern Ukraine